Pottery Art as an Implementation of Strengthening the Pancasila Student Profile: A Study Higher Education - Sopiandy, Dede; Murdiansyah, Eko Bambang; Ramly, Amisbah; Jasrudin, Jasrudin (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The purpose of this research is to provide a more profound understanding of the role of pottery in strengthening the collaboration dimension and improving students' understanding of Pancasila values. This research used a qualitative approach with a case study design. The pottery art village in Pagelaran Village, Malang Regency, served as the research site. The data collection techniques include observation, interviews, and documentation. The findings of the research are that pottery art has the potential to strengthen the cooperation dimension in the student profile of Pancasila. We expect the implementation of this project to foster collaboration, togetherness, and a caring attitude among students, pottery craftsmen, and the local community. In addition, the art of pottery can also be a means to strengthen the understanding and awareness of Pancasila values in students. Pottery art in Pagelaran Village, Malang Regency, has an important role in strengthening the cooperation dimension in the Pancasila student profile. The Pottery Art Village is a place where pottery artisans gather and work together. They help each other and work collaboratively in the process of making pottery.